2011
DOI: 10.1016/j.jafrearsci.2011.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Textural and knowledge-based lithological classification of remote sensing data in Southwestern Prieska sub-basin, Transvaal Supergroup, South Africa

Abstract: TM data and other medium spatial resolution satellite data are used in geological and lithologicalmineralogical classification on regular basis, although their usefulness is limited because of relatively coarse spectral resolution. In this contribution, we provide an example for the application of TM data for classification of rocks and minerals within the Neoarchean sedimentary and volcanic basin of Griqualand West, South Africa. An improved methodology is introduced that results in significantly higher class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…Previous studies have indicated the improvement of accuracy in classifying land cover when knowledge rules are used [31][32][33]. In our study, post classification results achieved very high accuracy and indicated the efficiency of this method in producing a high-accuracy LULC map (Figure 9).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Previous studies have indicated the improvement of accuracy in classifying land cover when knowledge rules are used [31][32][33]. In our study, post classification results achieved very high accuracy and indicated the efficiency of this method in producing a high-accuracy LULC map (Figure 9).…”
Section: Discussionsupporting
confidence: 67%
“…Finally, the differences in the spatial resolution between the combined datasets and the image processing implemented to unify this spatial resolution could be another source of misclassifications reported herein. Previous studies have indicated the improvement of accuracy in classifying land cover when knowledge rules are used [31][32][33]. In our study, post classification results achieved very high accuracy and indicated the efficiency of this method in producing a high-accuracy LULC map ( Figure 9).…”
Section: Discussionsupporting
confidence: 67%
“…In addition, mineralized limestone spectra show high reflectance in band 6 (OLI) and 4 (ASTER), and a weak absorption at 2200 nm, which coincides with bands 7 of OLI and 6 of ASTER, possibly due to the weak gypsum and clay alteration [20,26]. The spectral signature extracted from the ASTER data, which is also characterized by a deep absorption at 2330 nm (band 8), can be related to the presence of carbonate minerals [12,24] After examining different combinations of ratios, two Color Components (CCs) RGB (for each sensor) were chosen to better discriminate the existing lithological units and mineralized zones [9,27,28,29]. In CC1 (6/5, 7/6, 4/7) of OLI, the mudstone-sandstone is distinguished by a yellow-orange color, and it appears purple in CC3 [(6 + 8)/4; 8/4; 5/3] of ASTER, and it appears light blue-green in CC2 (5/4, 6/5, 7/2) of OLI.…”
Section: Selection Of Band Combinations For Discriminating Lithologiesmentioning
confidence: 92%
“…The sandstone-to-mudstone, which is rich of mica and clay minerals, is mapped by the ratios (6/5 of OLI) and (5/3 of ASTER), since its spectra show high reflectance in band 6 of OLI and band 5 of ASTER, against an absorption at 860 nm (band 5 of OLI) and 800 nm (band 3 of ASTER), corresponding to the near infrared region. This type of absorption is also due to the presence of iron oxides [22][23][24]. In comparison with other spectra, conglomerate shows a high reflectance in band 4 of OLI and band 3 of ASTER, and intense absorption of Al-OH type at 2200 nm (band 7 of OLI and band 6 of ASTER) due to mica or clay minerals [9,23,25], hence the ratios of (4/7 of OLI) and (3/6 of ASTER) are used to map this rock unit.…”
Section: Selection Of Band Combinations For Discriminating Lithologiesmentioning
confidence: 99%
“…Although it is not new to use remote sensing technique for lithological classification in geological investigation [2,22,23], many studies are limited, due to the coarse spatial/spectral resolutions of multispectral data, causing difficulties in accurately classifying rock units [22]. As a solution, multiple ancillary data with texture information, such as airborne geophysical data [24], DEM [25], and geomorphic feature [2], can be integrated with multispectral imagery for improved lithological classifications [22].…”
Section: Introductionmentioning
confidence: 99%